PERAN GURU DALAM PEMANFAATAN PERPUSTAKAAN SEBAGAI SUMBER BELAJAR UNTUK MENDUKUNG BUDAYA LITERASI MEMBACA DI SEKOLAH DASAR - Nurul Fitriyani; Rina Yuliana; Tatu Hilaliyah (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
This research is based on the government's efforts to foster a culture of literacy with the establishment of the School Literacy Movement "Gerakan Literasi Sekolah" (GLS) program where this program apart from cultivating a literacy culture also utilizes the library as a learning resource. Therefore this study aims to determine the teacher's role in the use of the library as a learning resource to support literacy culture at SDN Pancanegara schools for fifth grade students which is carried out by teachers, especially fifth grade teachers at Pancanegara Elementary School. This research uses a qualitative type, where the researcher as the main instrument through direct research with a naturalistic approach. This research consists of two stages, namely the preliminary stage and activity development/preliminary stage consisting of reference and field studies to obtain accurate information about the research problem. The development stage includes development activities and validation of research data collection. Data collection has been validated to be used for data collection. The results of the study show that the most important thing is the teacher's role in the process of learning activities that support the literacy culture shown by the teacher in the elementary school.